Emulgel: A Comprehensive Review for Topical Delivery of Hydrophobic Drugs - Nandgude Tanaji, Dilip (Asian Journal of Pharmaceutics (AJP), 2018)
In comparison with the other semisolid preparations, the use of gels has been emerged both in cosmetics and pharmaceutical preparations. When gel and emulsion used in the combined form, they are referred as Emulgel. Emulgel is the promising drug delivery system for the delivery of hydrophobic drugs. Emulgel is an emulsion which is gelled by mixing it with gelling agents. Many advantages of gels have the major limitation of delivery of hydrophobic drugs. Hence, to overcome this limitation, the emulsion based approach is being used. Emulgel is an interesting topical drug delivery system as it has dual release control system, i.e., gel and emulsion. Emulgels have several favorable properties for dermatological use such as being thixotropic, greaseless, easily spreadable, easily removable, emollient, nonstaining, long shelf life, transparent, and pleasing appearance. Hence, emulgels can be used as better topical drug delivery system over present systems. This review gives knowledge about emulgel including its properties, advantages, and formulation considerations and its recent advances in the research field.